Biological Evaluation of Air Quality of an Urban Ecosystem through Air Pollution Tolerance and Performance Index - Hafiza Komal Hanif; Sohaib Muhammad; Hsi-Hsien Yang; Muhammad Umer Farooq Awan; Shakil Ahmed; Muhammad Tayyab; Mahrukh Majeed; Summiya Faisal; Zaheer ud din Khan (Aerosol and Air Quality Research)
Abstract Purpose The rapid increase in urbanization leads to air pollution particularly in cosmopolitan city like Lahore (Pakistan) which poses a significant threat to human health. Air pollution has negative impacts on roadside vegetation and the environment. However, plants growing along roadsides have the ability to mitigate air pollution. Methods For assessing the air quality of the urban ecosystem through road side plantation two indices Quantitative i.e. Air pollution Tolerance Index (APTI) and qualitative one i.e., Anticipated Performance Index (API) was used. Along with these Total protein content and proline amount was also assessed under high stress of particulate pollution. Results Six different plant species were selected for the study: Alstonia scholaris, Callistemon lanceolatus, Cassia fstula, Ficus religiosa, Mimusops elengi and Polyalthia longifolia. Leaves of these selected plant species were collected from five distinct sites (four experimental and one control site). Ficus religiosa was found to be the best performer, while Mimusops elengi and Callistemon lanceolatus were resulted as good performers. The highest and lowest amounts of proline content were measured for Ficus religiosa and Callistemon lanceolatus, while protein content was found reduced at highly polluted sites. Conclusions Screening of existing landscape of any cosmopolitan area with high APTI and API values will aid in green urban development by supporting conservation efforts aimed at protecting biodiversity and reducing the harmful impacts of air pollution on the environment and public health. Graphical abstract